Tinjauan Yuridis Terkait Ketidakabsahan Perkawinan Kedua yang Fasid Karena Tidak Ada Izin Poligami dari Pengadilan Agama ditinjau dari Undang – Undang Perkawinan dan Hukum Islam - Kinata Kinar Andreas Perangin – Angin; Artaji Artaji; Fatmi Utarie Nasution (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
This study is motivated by the high rate of marriage in Indonesia. Marriage is a sacred activity because through marriage there will be new family relationships and the consequences that arise from the marriage. The validity of a marriage in Indonesia is highly dependent on the provisions of each religion recognized in the Unitary State of the Republic of Indonesia. In Islam, a man can practice polygamy if he has met the existing conditions. Polygamy will have an impact on the validity of a marriage if the existing conditions are not met by the couple. Therefore, the validity of a marriage is very necessary in the system of the state of law.